Cancer recurrence or aggravation following COVID-19 vaccination - Parisa Soleimani; Sepideh Yadollahifarsani; Mahsa Motieian; Mahshid Sadat Chenarani Moghadam; Shahrzad Alimohammadi; Azadeh Khayyat; Mohammad Ali Esmaeil Pour; Sina Neshat; Narges Alsadat Marashi; Leila Mahmoodnia; Rohollah Masomi (Society of Diabetic Nephropathy Prevention, 2023)
COVID-19 infection has been a global health issue in the past recent years and numerous topics are studied in order to discover its pathophysiology and potential side effects. The potential for disease recurrence following the administration of the COVID-19 vaccine is one of the issues that has recently attracted attention. Several studies have revealed that the COVID-19 vaccines, like other vaccines, may have side effects and, in some cases, they may even deteriorate the underlying illnesses, such as rheumatic diseases, autoimmune diseases, and cancers. The effectiveness and safety of the COVID-19 vaccine for patients with malignancies are one of the factors that are considered regarding this vaccine. Lymph node involvement, disease recurrence, and potential paraclinical changes after receiving the COVID-19 vaccine are some of the concerns of patients with malignancy. In this mini-review, we attempted to investigate cases of cancer recurrence or recovery as well as lymphadenopathy following vaccination.